2015
DOI: 10.1002/nur.21701
|View full text |Cite
|
Sign up to set email alerts
|

Hard is Normal: Military Families' Transitions Within the Process of Deployment

Abstract: US military deployments have become more frequent and lengthier in duration since 2003. Over half of US military members are married, and many also have children. The authors sought to understand the process of deployment from the perspective of the military family. After a thorough search of the literature, 21 primary research reports of 19 studies with an aggregate sample of 874 were analyzed using qualitative metasynthesis. The deployment process was experienced in four temporal domains. The military family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…On one hand, prior cross-sectional work has documented correlations between trust and relational uncertainty among civilians in everyday situations (Dainton & Aylor, 2001; Mikkelson et al, 2016; Sheldon & Pecchioni, 2014), which offers evidence in favor of generalizability. On the other hand, the challenges embedded in the post-deployment transition (e.g., Knobloch & Theiss, 2012; Yablonsky et al, 2016) may make reunion a risk regulation situation particularly likely to activate the trust system (e.g., Cavallo et al, 2014; Murray et al, 2013). For example, reuniting military couples may discover problems such as infidelity, lack of commitment, or personality changes in one or both partners (e.g., Balderrama-Durbin et al, 2017; Kachadourian et al, 2015; Knobloch & Theiss, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, prior cross-sectional work has documented correlations between trust and relational uncertainty among civilians in everyday situations (Dainton & Aylor, 2001; Mikkelson et al, 2016; Sheldon & Pecchioni, 2014), which offers evidence in favor of generalizability. On the other hand, the challenges embedded in the post-deployment transition (e.g., Knobloch & Theiss, 2012; Yablonsky et al, 2016) may make reunion a risk regulation situation particularly likely to activate the trust system (e.g., Cavallo et al, 2014; Murray et al, 2013). For example, reuniting military couples may discover problems such as infidelity, lack of commitment, or personality changes in one or both partners (e.g., Balderrama-Durbin et al, 2017; Kachadourian et al, 2015; Knobloch & Theiss, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been limited research to inform intervention on coparenting in the context of wartime deployment (Lester & Flake, 2013; Wadsworth et al, 2012). Thus, the aim of the current qualitative study is to characterize the rich lived experiences and stressors of coparenting across the deployment cycle (DeVoe & Ross, 2012; Yablonksi, Barbero, & Richardson, 2015).…”
Section: Coparenting and The Deployment Lifecyclementioning
confidence: 99%
“…By understanding the emotional cycle of deployment (Morse, 2006) and the types of emotional challenges experienced before deployment day, this PEP-CEP framework can further explain how different preparatory approaches may affect the subsequent phases of deployment. Most research seems to reflect that military wives emotionally detach or withdraw before deployment (e.g., Morse, 2006;Sahlstein et al, 2009;Yablonsky et al, 2016), yet not every military wife in this study adopted this PEP approach.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research identified how some military wives elect to emotionally detach, withdraw, or numb themselves, like turning off an emotional "circuit breaker," so that they do not become emotionally overwhelmed leading up to deployment (Morse, 2006;Peebles-Kleiger & Kleiger, 1994;Sahlstein et al, 2009;Vincenzes et al, 2014;Yablonsky et al, 2016). Therefore, how military wives invest their energy preparing for deployment, by engaging in both taskoriented and emotional preparations, may create a firm foundation for successfully managing deployment-related stressors throughout the subsequent phases.…”
Section: Preparation For Deployment Daymentioning
confidence: 99%